Optimizing a low-temperature preservation technique for Bacillus anthracis strains - A. P. Rodionov; E. A. Artemeva; L. A. Melnikova; D. M. Sahibullina (Ветеринария сегодня)
The use of pure microbial cultures is associated with the following key challenges: storage, transportation and resuscitation after a long-term preservation. The currently used anthrax vaccines are produced using various strains of Bacillus anthracis. According to the storage passport data, anthrax strains are now stored in 30–40% glycerin solutions, which helps to preserve a sufficient number of viable cells without losses to their pathogenic properties for three years. It is obviously an urgent task to develop a long-term preservation technique for Bacillus anthracis strains. The aim of this study was to optimize a low-temperature preservation method for Bacillus anthracis strains that ensures viability and no losses to biological properties of the pathogen. Two vaccine strains of Bacillus anthracis were selected for the research: i.e. K-STI-79 and 55-VNIIVViM and two cryoprotective media (No. 1 – 15% glycerin solution with 15% glucose solution and No. 2 – 30% neutral glycerin solution in saline solution). At first biological properties of the strains were studied and the number of viable cells was calculated. Later on, the strains were placed into low-temperature preservation facilities, at the temperature of –40 and –70 °C. Six months later, the effect of three thawing cycles on viability and biological properties of the agent was tested: i.e. at room temperature (22 ± 2) °C, in a water bath at a temperature of (37 ± 1) °C and in a household refrigerator at a temperature of (6 ± 2) °C. As demonstrated, the best option is to preserve the cells at –70 °C and thaw them in a water bath at (37 ± 1) °C. Further research will be focused on duration of the low-temperature preservation that will ensure appropriate viability and biological properties of the pathogen.